1996
DOI: 10.1046/j.1523-1739.1996.10020414.x
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a Regional Frog Fauna in the Yosemite Area of the California Sierra Nevada, USA

Abstract: There has been much concern about widespread declines among amphibians, but efforts to determine the extent and magnitude of these declines have been hampered by scarcity of comparative inventory data. We resurveyed a transect of the Sierra Nevada mountains in western North America that was carefully studied in the early 1900s. Our comparisons show that at least five of the seven frog and toad species in the area have suffered serious declines. One species has disappeared from the area entirely and a second sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
185
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(194 citation statements)
references
References 29 publications
3
185
1
3
Order By: Relevance
“…1) and yet has declined dramatically (34)(35)(36). The disjunct southern populations are federally listed as endangered, and the listing of the remaining Sierra Nevada populations as endangered was recently found to be ''warranted'' (37).…”
mentioning
confidence: 99%
“…1) and yet has declined dramatically (34)(35)(36). The disjunct southern populations are federally listed as endangered, and the listing of the remaining Sierra Nevada populations as endangered was recently found to be ''warranted'' (37).…”
mentioning
confidence: 99%
“…nib.gov/docs/1999/107p799-803rowe/abstrac hrml Several regional and global reviews have reported extinctions, extirpations, and serious declines ofa number ofamphibian species and their populations (1)(2)(3)(4)(5)(6). The detrimental effect that habitat destruction has on amphibian populations is undeniable (7).…”
mentioning
confidence: 99%
“…Populations in Western Europe, the United Kingdom and North America for instance all showed declines (Houlahan et al 2000). Also high-altitude populations in the Sierra Nevada in the United States have experienced strong declines for reasons largely unknown (Drost and Fellers 1996). Direct and indirect impacts of climate change have been suggested as reasons for the decline of other amphibian populations (Pounds et al 1999;Walther et al 2002).…”
Section: Amphibiansmentioning
confidence: 99%